Determination of 43 pesticide residues in intact grape berries (Vitis Vinifera L.) by using an ultrasound-assisted acetonitrile extraction method followed by LC–MS/MS. (October 2022) - Du, Yuting; Wang, Qiang; Yang, Guiling; Han, Fuliang
Abstract: An ultrasound-assisted acetonitrile extraction method was applied for the determination of 43 pesticide residues in intact grape berries ( Vitis Vinifera L.) by liquid chromatography-tandem mass spectrometry (LC–MS/MS). The results showed that ultrasound-assisted extraction from intact grape berries exhibited better efficiency than extraction from homogenized grape berries. Matrix-matched calibration curves were applied from 0.01 to 200 μg/L and determination coefficients (R 2 ) were greater than 0.99. The recovery values were 70.6%–119.7% with a relative standard deviation (RSD) range of 0.02%–9.92%. The limits of detection (LODs) and limits of quantification (LOQs) ranged between 0.005 μg/kg and 0.2 μg/kg, and between 0.10 μg/kg and 10 μg/kg, respectively. The method was applied in the analysis of wine grape samples from three different regions of China. A total of 10 pesticides were detected in samples during fruit ripeness. Highlights: Pesticide residues were directly extracted in intact grape berries. An ultrasound-assisted acetonitrile extraction method was performed. Multiple pesticide residues were detected in the commercial wine grapes. Change rules of pesticide residues in wine grapes during veraison were studied.